COVID-19 and indigenous peoples: An analysis from social anthropology perspective - Barandela, Ana Clara (2022)
: In this article we describe and analyze several impacts that coronavirus has produced over some aboriginal population from America and Argentina, taking into consideration, their responses, understanings and developed strategies, related to state policies. Likewise, we develop an analytical description of possibilities that the ethnographic method, belonging to the anthropological sciences, offers, for a multidimensional approach. This method also makes it possible to advise, evaluate and monitor certain public policies. When it comes to the information obtained, it was acquired using several secondary sources of data and interviews posted on the Internet.